An information-motivation-behavioral skills analysis of diet and exercise behavior in Puerto Ricans with diabetes. - Osborn, Chandra Y; Rivet Amico, K; Fisher, William A; Egede, Leonard E; Fisher, Jeffrey D (Journal of health psychology, 2010)
Frameworks are needed to inform diabetes self-care programs for diverse populations. We tested the Information-Motivation-Behavioral Skills (IMB) model in a sample of Puerto Ricans with Type 2 diabetes (N = 118). Structural equation models evaluated model fit and interrelations between IMB constructs. For diet behavior, information and motivation related to behavioral skills ( r = 0.19, p < .05 and r = 0.39, p < .01, respectively); behavioral skills related to behavior (r = 0.42, p < .01 and r = 0.32, p < .05); and behavior related to glycemic control (r = -0.26, p < .05). For exercise, personal motivation related to behavioral skills (r = 0.53, p < .001), and behavioral skills related to behavior (r = 0.45, p < .001). The IMB model could inform interventions targeting these behaviors in diabetes.
Keywords: Aged; Blood Glucose; Diabetes Mellitus, Type 2; Exercise Therapy; Female; Hispanic Americans; Humans; Information Dissemination; Male; Middle Aged; Motivation; Puerto Rico; Risk Reduction Behavior; Self Care; United States